Fusi Bahasa dan Identitas: Analisis Pemakaian Bahasa Inggris-Campur dalam Komunikasi Generasi Z - Husnita, Sri Rezeky Indiani; Simarmata, Yohana Vanessa Rebecca; Setijadi, Naniek Novijanti (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The phenomenon of mixing Indonesian and English in the everyday communication of today’s youth reflects a shift in language practices closely tied to the construction of cultural identity in the era of digital globalization. Generation Z, born into a digital and multicultural environment, utilizes code-mixing not only as a communication tool but also as an expression of lifestyle, a symbol of social affiliation, and a form of identity negotiation between local and global values. This study aims to: (1) analyze the use of code-mixing as a reflection of the identity dynamics of Generation Z; (2) explain the process of identity negotiation through modernity, localization, and resistance to linguistic purism; and (3) illustrate the role of social media in accelerating the normalization of linguistic fusion practices. Using a qualitative approach, this study employs literature review and content analysis of Generation Z’s digital communication on social media. The findings reveal that code-mixing functions as a medium of hybrid identity expression, integrating elements of local and global cultures, and simultaneously serving as a symbol of social status, linguistic creativity, and group solidarity. The study concludes that the practice of code-mixing among Generation Z represents a tangible manifestation of cultural identity fusion, which is dynamic and reflective of contemporary societal changes. These findings contribute to the development of intercultural communication theory and offer valuable insights for formulating language policies that are adaptive to the social dynamics of the younger generation.